2015
DOI: 10.1016/j.neuron.2014.11.027
|View full text |Cite|
|
Sign up to set email alerts
|

Parkinson’s Disease Genes VPS35 and EIF4G1 Interact Genetically and Converge on α-Synuclein

Abstract: Summary Parkinson’s disease (PD) is a common neurodegenerative disorder. Functional interactions between some PD genes, like PINK1 and parkin, have been identified, but whether other ones interact remains elusive. Here we report an unexpected genetic interaction between two PD genes, VPS35 and EIF4G1. We provide evidence that EIF4G1 upregulation causes defects associated with protein misfolding. Expression of a sortilin protein rescues these defects, downstream of VPS35, suggesting a potential role for sortili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
169
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(187 citation statements)
references
References 75 publications
18
169
0
Order By: Relevance
“…13 Rather, the resultant pathologies are protein-specific: 1) improper folding or maintenance of structure can lead to a protein's improper degradation, such as occurs in cystic fibrosis (cystic fibrosis transmembrane conductance regulator protein) and Gaucher disease (β-glucosidase), 14,15 ; 2) a dominant negative mutation that leads to a hypo-functional peptide, which occurs in epidermolysis bullosa simplex (keratin), 16 ; 3) a gain of toxicity function, such as occurs with certain variants of APOE4 in Alzheimer disease (AD), 17 ; and 4) the accumulation of multiple, misfolded species resulting in formation of toxic polypeptides and aggregates, such as occurs with many of the neurodegenerative diseases. 18,19 …”
Section: Introduction: Proteotoxicitymentioning
confidence: 99%
“…13 Rather, the resultant pathologies are protein-specific: 1) improper folding or maintenance of structure can lead to a protein's improper degradation, such as occurs in cystic fibrosis (cystic fibrosis transmembrane conductance regulator protein) and Gaucher disease (β-glucosidase), 14,15 ; 2) a dominant negative mutation that leads to a hypo-functional peptide, which occurs in epidermolysis bullosa simplex (keratin), 16 ; 3) a gain of toxicity function, such as occurs with certain variants of APOE4 in Alzheimer disease (AD), 17 ; and 4) the accumulation of multiple, misfolded species resulting in formation of toxic polypeptides and aggregates, such as occurs with many of the neurodegenerative diseases. 18,19 …”
Section: Introduction: Proteotoxicitymentioning
confidence: 99%
“…Interestingly, functional studies of trafficking proteins implicate their role in α-syn-mediated cell death (11)(12)(13). Whereas these studies imply that vesicle trafficking deficits may lead to α-syn accumulation, no studies have demonstrated a mechanistic linkage between these processes.…”
mentioning
confidence: 99%
“…TIF4631 and TIF4632, of which TIF4631 is the most closely related to the human EIF4G1. To investigate the function of these genes in more detail, Dhungel et al (2015) performed two genetic screens with respectively vps35∆ and tif4631∆ yeast strains. As expected, the major functional groups, identified from the vps35∆ screen, included protein targeting and vacuolar transport while transcription and translation groups were identified by means of the tif4631∆ screen.…”
Section: Yeast Models To Study Parkinson's Disease Associated Genesmentioning
confidence: 99%